Altered Arginine/Nitric Oxide Pathway in Children Diagnosed Attention Deficit Hyperactivity Disorder, and the Effect of 10 Weeks Methylphenidate Treatment - Doneray, Ebru; Yazici, Kemal Utku; Yazici, Ipek Percinel; Ustundag, Bilal (Korean Coll Neuropsychopharmacology, 2022)
Objective: In this study, we investigated the levels of arginine, nitric oxide (NO), asymmetric dimethylarginine (ADMA), and adrenomedullin that are presumed to play a role in attention deficit hyperactivity disorder (ADHD) etiology, and to compare the findings with healthy controls. Methods: Thirty ADHD patients and thirty healthy control subjects aged 6-12 years were included in the study. Sociodemographic data form, Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version; Conners' Parent/Teacher Rating Scale-Revised: Long Form; Children's Depression Inventory; and The State-Trait Anxiety Inventory for Children were applied to all cases. All participants included in the study were evaluated in terms of their serum arginine, NO, ADMA, and adrenomedullin levels. Subsequently, methylphenidate treatment was started in ADHD patients and blood parameters were tested again in the tenth week of treatment. Results: At the start of the study, arginine and ADMA levels were significantly higher and NO and adrenomedullin levels were significantly lower in the ADHD group compared to the control group. Post-treatment arginine and ADMA levels were found to be significantly lower than in the pre-treatment period. There were no significant differences in NO and adrenomedullin levels before and after treatment. There was no correlation between scale scores and blood parameters. Conclusion: These variations in the blood parameters of the ADHD group seem to be worth further investigation. Studies to be conducted with larger sample groups after longer-term treatment may provide new information about the alterations in neurobiological processes related to ADHD etiology and treatment.
Keywords: Attention deficit hyperactivity disorder; ADMA; Adrenomedullin; Arginine; Nitric oxide